The role of Persian causative markers in the acquisition of English causative verbs - Ali Akbar Jabbari; Mohammad Javad Rezaie (Journal of English Language Teaching and Learning, 2012)
This project investigates the relationship between lexical semantics and causative morphology in the acquisition of causative/inchoative-related verbs in English as a foreign language by Iranian speakers. Results of translation and picture judgment task show although L2 learners have largely acquired the correct lexico-syntactic classification of verbs in English, they were constrained by the morphological patterns of their first language (L1) when learning zero morphology, especially with causative/inchoative verbs. Results also show the lack of the learners' proficiency level in all causative/inchoative contexts and in almost all contexts in grammatical judgment task.The transitivity errors documented are analogous to the overgeneralization errors reported in the L1 and L2 acquisition literature of English and other languages. In this study, we also suggest that L2 learners are atuned to the rich morphology of Persian and that the acquisition of derivational morphology and lexical semantics are not dissociated in these interlanguage grammars.